1986
DOI: 10.4039/ent1181221-12
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF AGE, EGG DEVELOPMENT, AND MATING ON CALLING BEHAVIOR OF THE BERTHA ARMYWORM, MAMESTRA CONFIGURATA WALKER (LEPIDOPTERA: NOCTUIDAE),

Abstract: The effects of age, egg development, and mating on calling behavior of the bertha armyworm, Mamestra configurata Walker, were studied at 20°C, 60% RH, and a 16-h L: 8-h D photoperiod. Most virgin females called and copulated for the first time during the second or third scotophase after emergence. The first copulation was 17.0 ± 0.2 h (mean±SE) long and was terminated within 1 h after lights off in the scotophase following the initiation of copulation. The ovaries contained the first chorionated eggs before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
3
14
0
3
Order By: Relevance
“…brassicae is also similar to that of related Mamestra species. Mamestra brassicae shows changes in calling behaviour with increasing age similar to those in M. configurata Walker (Howlader & Gerber, 1986b). In this species also, the onset of calling advances in time with decreasing length of scotophase (Gerber & Howlader, 1987).…”
Section: Discussionmentioning
confidence: 62%
“…brassicae is also similar to that of related Mamestra species. Mamestra brassicae shows changes in calling behaviour with increasing age similar to those in M. configurata Walker (Howlader & Gerber, 1986b). In this species also, the onset of calling advances in time with decreasing length of scotophase (Gerber & Howlader, 1987).…”
Section: Discussionmentioning
confidence: 62%
“…Some features of the calling and courtship behavior in P. citrella females, particularly wing movements, were previously observed in Lymantria dispar (L.) (Charlton & Cardé 1990), Mamestra configurata Walker (Howlander & Gerber 1986), and Bucculatrix thurberiella Busck (Lingren et al 1980). Male wings overlapping over female wings during copulation have been previously observed in B. thurberiella (Lingren et al 1980).…”
Section: Description Of Calling Courtship and Copulation Behaviormentioning
confidence: 84%
“…Others report the proportion of females calling (Hendrikse 1979) or how early calling begins each night (Delisle and McNeil 1987;Kou and Chow 1987;Delisle 1992). Several studies report changes in calling bout number and bout length (Howlader and Gerber 1986;Jacas and Peña 2002;Mazor and Dunkelblum 2005;Ming et al 2007), with calling bout defined as a period of time over which a female is observed in the characteristic position of raising her abdomen and periodically everting her ovipositor.…”
Section: Empirical Evidence On Female Signaling Effortmentioning
confidence: 99%